1994
DOI: 10.1007/bf01061991
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding complications to long-term oral anticoagulant therapy

Abstract: Objective: To evaluate the incidence of bleeding complications in recent randomized trials on oral anticoagetlant treatment for prevention of arterial thromboembolism. Data sources: International publications on studies of prevention. of arterial thromboembolism by oral anticoagulant therapy. Study selection and data extraction: Randomized trials an oral anticoagulant therapy in patients with atrial fibrillation, recent myocardial infarction, and prosthetic heart valves were selected. For comparison older nonr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 27 publications
1
14
1
1
Order By: Relevance
“…25,26 However, the prevalence rates of major GI or IC bleeding events in the present study sample were slightly higher than those observed in previously published clinical trials. In a recent meta-analysis of the efficacy and safety of antithrombotic therapy in AF, the incidence rates for IC and major extracranial hemorrhage for patients receiving adjusteddose warfarin therapy were 0.2% and 1.0%, 27 compared with 0.4% and 1.9% in the present study.…”
Section: Limitationscontrasting
confidence: 55%
“…25,26 However, the prevalence rates of major GI or IC bleeding events in the present study sample were slightly higher than those observed in previously published clinical trials. In a recent meta-analysis of the efficacy and safety of antithrombotic therapy in AF, the incidence rates for IC and major extracranial hemorrhage for patients receiving adjusteddose warfarin therapy were 0.2% and 1.0%, 27 compared with 0.4% and 1.9% in the present study.…”
Section: Limitationscontrasting
confidence: 55%
“…In a review of trials to evaluate haemorrhaging during warfarin therapy, the mean incidence of fatal and major haemorrhaging was 0.5% and 1.7% per year, respectively (Gullov et al 1994). Therefore, it is not surprising that surgeons worry about the possibility of sight-threatening complications due to intra or postoperative haemorrhaging.…”
Section: Discussionmentioning
confidence: 99%
“…•이경훈 2 •손기호 3 •조현정 5 •온영근 4 •김준수 4 •이수연 1,3 성균관대학교 의과대학 삼성서울병원 진단검사의학교실 1 •분자세포생물학교실 2 •내과 4 •임상약리학, 임상시험센터 3 , 건양대학교 의과대학 진단검사의학교실 5 …”
unclassified
“…Inadequate or excessive anticoagulation may result in substantial morbidity and mortality due to thromboembolic complications or bleeding [3,4]. Life-threatening bleeding episodes after initiation of warfarin therapy have been reported in approximately 12% of patients; furthermore, elderly patients are especially vulnerable to such events, and there is also a substantial risk of developing warfarin resistance [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%